A 120 MHz fast automatic tuning CMOS active-RC lowpass filter. (March 2023) - Yesil, Ercem; Zencir, Ertan
Abstract: In this paper, a fast automatic cutoff frequency calibrating, CMOS lowpass filter with linear-in-dB tunable gain and constant in-band group delay is presented. The automatic frequency tuning (AFT) circuit can successfully tune the cutoff frequency to 120 MHz with less than 4.7% error. In-band group delay variation is handled using a capacitor process variation detection circuit (CPVD), and the overall tuning time is less than 700 ns. The design is done using STM PD-SOI 130 nm CMOS process, and the supply voltage is 1.2 V with a total power consumption of 21.7 mW. The overall filter provides a programmable linear-in-dB gain of 0.5 dB to 17.6 dB range with a cutoff tuning range of 80 to 180 MHz. The in-band group delay variation is below 500 ps with an adjacent channel ratio (ACR) of 85 dB. The spurious free dynamic range (SFDR) is over 66.6 dBc. The active area of the filter with tuning is 0.171 mm 2 .